Design of a balanced scorecard for a service microenterprise in Tenosique, Tabasco, México: a case study - Ortiz García, Pedro Luis (2025)
The balanced scorecard is a management control system that encompasses key performance indicators organized into four main perspectives: financial, process, customer, and learning and growth. The micro-food business under study needs to make substantial improvements in its daily operations and management to adapt to changes and ensure its continued growth. Based on a review of the literature and the data collected, a method for designing a balanced scorecard is proposed. It is concluded that the effectiveness of this method's design in a company of this nature is determined by its management experience, commitment, and use of human and financial resources.